Genera of fungivorous Phlaeothripinae (Thysanoptera) from dead branches and leaf-litter in Australia - Mound, Laurence A.; Dang, Li-Hong; Tree, Desley J. (Zootaxa, 2013)
An illustrated key is provided for the identification of 39 genera of Thysanoptera—Phlaeothripinae with species that live in association with dead branches and leaf-litter in Australia and are considered to be fungus-feeding. Seven of these gen-era are not previously recorded from this continent, including un-named species of Deplorothrips, Malacothrips, Mystro-thrips, Preeriella and Tylothrips, together with Azaleothrips lepidus Okajima and Terthrothrips ananthakrishnani Kudo. A brief generic diagnosis is provided for each genus, together with comments on systematic problems and numbers of species.